Legal Implications of Proving the Status of Non-Marital Children through DNA Tests in the Indonesian Civil Law System - Noval, Cepi; Santiago, Faisal (Jurnal Greenation Sosial dan Politik, 2025)
The development of genetic technology, especially DNA testing, presents new opportunities in proving civil law, especially related to the status of children non-marital. In the context of Indonesian law, the regulation of non-marital children still gives rise to various interpretations, especially in terms of determining civil relations with the biological father. The Constitutional Court through Decision No. 46/PUU-VIII/2010 and the latest Decision No. 69/PUU-XIII/2015 has opened up the space for recognition of children non-marital, but has not fully regulated the mechanism of proof comprehensively, especially in cases involving alleged adultery. This study aims to analyse the status of children non-marital after the Constitutional Court's decision and the extent to which DNA tests can be used as evidence to determine the child's civil rights, whether as main evidence or only in supporting nature. The research method used is normative juridical with a legislative approach and a study of court decisions. The results show that DNA tests have high scientific validity, but are still legally positioned as supporting evidence, not a single stand-alone evidence. This is in line with Article 1865 of the Civil Code and Article 164 of the Civil Code which places evidence in a certain hierarchy. In conclusion, although DNA tests have the potential to strengthen the civil claims of non-marital children against their biological fathers, there is still a need for voluntary recognition or through a court order that comprehensively assesses the entire set of evidence. Therefore, further regulation is urgently needed to ensure legal certainty and protection of the rights of children non-marital in Indonesia.